(untitled) - Isoda, Michifumi (Chiyoda-ku, Tokyo, 2017)
True stories of three little-known Japanese of the Edo period who lived lives of sublime selflessness and purity, blurring the boundary between self and others. Merchant Kokudaya Juzaburo comes up with a brilliant scheme to rescue his dying town from poverty. He and others go deep into debt, risking all to raise money for the cash-strapped daimyo and receive annual interest in return.
Keywords: Nhật Bản,Japan; Lịch sử,History